2021
DOI: 10.5765/jkacap.210010
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Quantitative Electroencephalogram in the Diagnosis and Subgrouping of Attention-Deficit/Hyperactivity Disorder

Abstract: Attention-deficit/hyperactivity disorder (ADHD) leads to functional decline in academic performance, interpersonal relationships, and development in school-aged children. Early diagnosis and appropriate intervention can significantly reduce the functional decline caused by ADHD. Currently, there is no established biological marker for ADHD. Some studies have suggested that various indicators from the quantitative electroencephalogram (QEEG) may be useful biological markers for the diagnosis of ADHD. Until the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 60 publications
1
4
0
Order By: Relevance
“…This supports the crucial role CFC has in linking relevant brain regions, which results in sensory information integration and neural computation required in tasks such as attention, learning, working memory, and memory consolidation [ 20 , 43 , 44 ]. PAC is a means of sequence encoding, storage, retrieval of information, and communication between local networks, as well as macroscale systems in the brain [ 45 ].…”
Section: Introductionsupporting
confidence: 55%
“…This supports the crucial role CFC has in linking relevant brain regions, which results in sensory information integration and neural computation required in tasks such as attention, learning, working memory, and memory consolidation [ 20 , 43 , 44 ]. PAC is a means of sequence encoding, storage, retrieval of information, and communication between local networks, as well as macroscale systems in the brain [ 45 ].…”
Section: Introductionsupporting
confidence: 55%
“…The analysis of their performance in the working memory test revealed no difference between the ADHD and the control groups ( Figure 1 A); however, there was high heterogeneity in the performance of the group with ADHD symptoms. It is known that ADHD presents high etiological diversity, as well as variation in the neurophysiological correlates of this disorder, in different studies [ 21 , 25 , 26 , 27 ]. Therefore, we assessed whether our ADHD subjects were indeed heterogeneous through their performance in a working memory test.…”
Section: Discussionmentioning
confidence: 99%
“…There are articles reporting the classification of ADHD patients based on their qEEG [ 25 , 26 , 27 ]. Our work suggests that different neurophysiological correlates also imply different cognitive affectation in ADHD patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, although it does not constitute a diagnostic test per se for ADHD (Adamou et al, 2020), the QEEG could play a relevant role in its differential diagnosis, as well as other tests (Chiarenza, 2021;Lenartowicz & Loo, 2014;McVoy et al, 2019), and provide clinical information relevant to the patient's approach (Loo & Makeig, 2012). In addition, several studies have found patterns (Arns et al, 2008;Bong & Kim, 2021;del Campo et al, 2012) using the EEG spectral analyses that could -or could not-be considered as the electroencephalographic endophenotypes of ADHD and that, despite not having a clear diagnostic utility, would have a classificatory and even a prognostic utility. (Arns, 2012b;Arns & Olbrich, 2014;Slater et al, 2022).…”
Section: Use Of the Qeeg In The Differential Diagnosis Of Adhdmentioning
confidence: 99%